Alkylation of anisole with 1-hexene and 1-hexanol over zeolite H-beta - Surse, P. V.; Wagholikar, S.; Mayadevi, S.; Sivasanker, S. (Reaction Kinetics Mechanisms and Catalysis, 2011)
An examination of the kinetics of the alkylation of anisole with 1-hexene and 1-hexanol to produce alkylates over zeolite H-beta is presented. Anisole alkylation is found to occur by a set of parallel reactions when hexene is used as the alkylating agent. When hexyl alcohol is the alkylating agent, the reaction follows a multi-step parallel-series mechanism to form monoalkylates and dihexylether. With 1-hexene, a group of isomeric alkylates, viz., ortho-2-hexyl anisole (2-OHA), ortho-3-hexyl anisole (3-OHA), para-2-hexyl anisole (2-PHA), and para-3-hexyl anisole (3-PHA) was obtained. With hexanol, the olefin (hexene) and dihexyl ether were obtained additionally. The influence of process parameters like temperature, catalyst quantity, and alkylating agent on reaction behavior is reported.
Keywords: Alkylation; Anisole; H-beta; Hexene; Hexyl alcohol